SISTEM PENGAMBILAN KEPUTUSAN PEMILIHAN SEPEDA MOTOR MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) Studi Kasus: Sepeda Motor Sport Y amaha CB Rajawali Graha Motor - Bayu Rianto (Program Studi Teknik Industri, 2018)
Today the development of information technology has been so rapid. The rapid development of not only hardware and software technology, but also the method of computing. One method of computing that is quite developed today is the method of decision-making system. In information technology decision-making system is a branch of science that lies between information systems and intelligent systems. Motorcycles at this time is very rapidly growing not inferior to the development of information technology itself, motorcycles have their own types and specifications, such as the type of motor sport that is currently a prima donna in the community. Motorcycle selection system at this time is only done by choosing directly and there is no support system in making the decision which motor is the best to be chosen as a vehicle to be used or selected.